Indole acids as a novel PDE2 inhibitor chemotype that demonstrate pro-cognitive activity in multiple species. Issue 6 (1st April 2018) - Stachel, Shawn J.; Egbertson, Melissa S.; Wai, Jenny; Machacek, Michelle; Toolan, Dawn M.; Swestock, John; Eddins, Donnie M.; Puri, Vanita; McGaughey, Georgia; Su, Hua-Poo; Perlow, Debbie; Wang, Deping; et al.
Graphical abstract: An internal HTS effort identified a novel PDE2 inhibitor series that was subsequently optimized for improved PDE2 activity and off-target selectivity. The optimized lead, compound4, improved cognitive performance in a rodent novel object recognition task as well as a non-human primate object retrieval task. In addition, co-crystallization studies of close analog of4 in the PDE2 active site revealed unique binding interactions influencing the high PDE isoform selectivity. Abstract: An internal HTS effort identified a novel PDE2 inhibitor series that was subsequently optimized for improved PDE2 activity and off-target selectivity. The optimized lead, compound4, improved cognitive performance in a rodent novel object recognition task as well as a non-human primate object retrieval task. In addition, co-crystallization studies of close analog of 4 in the PDE2 active site revealed unique binding interactions influencing the high PDE isoform selectivity.